Design and Structural Characterization of Novel Azo-Theophylline as Acid-Base Indicator - Manulla, Mohnned hamady; Abbas, Alyaa Khidir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Novel heterocyclic acid-base indicators 8-[3-(phenol)azo] theophylline (PAT) and 8[1-(6-sulfonic acid naphthalene) azo] theophylline (SAT) were synthesized through the reaction between m-amino phenol and 1-amino naphthalene -6-sulfonic acid with sodium nitrite to form the diazonium salt at a temperature 0-5˚C in an acidic medium, then a coupling process between the diazonium salt and theophylline compound to produce pigments at the same temperature while maintaining the PH level at 5-6. This study aims to prepare acid-base indicators based on azo dyes. The structural features of these indicators were examined via elemental analyses [FTIR, UV-Vis, and HNMR] spectroscopies, thermal analysis (TGA), and scanning electron microscopy (SEM); the dyes showed good Nanoscale properties. The efficiency of these compounds to act as acid-base indicators has been investigated. This is due to the ability of azo compounds to change their colors in acid and alkaline environments. Compounds SAT and PAT showed good sensitivity towards changing the value of PH, and the color contrast was apparent. The research aims to prepare acid-base indicators based on azo dyes.